Evidências científicas sobre a influência cultural nos cuidados às crianças - Isabella Joyce Silva de Almeida; Bruna de Souza Buarque; Tatiane Gomes Guedes; Gabriela Cunha Schechtman Sette; Ana Márcia Tenório de Souza Cavalcanti (Universidade Federal do Ceará, 2017)
Objective: to analyze the scientific evidence on cultural influence in child care. Methods: integrative review of the literature with metassynthesis, carried out in six databases, without limits regarding the year of publication, using the descriptors "Culture" and "Child Care", in the Portuguese, English and Spanish languages. Data evaluated were through content analysis and in light of the constructs of Leininger's theory. Results: seven articles were selected, from which two categories emerged: interface between professional care systems and culture; and interface between generic care systems and culture. Conclusion: culture influences the general care given to children, especially related to respiratory problems, malnutrition and burns. The use of medicinal plants, homemade teas and taking to a folk healer are examples of popular practices that permeate the routine of care provided to children.